2017
DOI: 10.53841/bpstcp.2017.13.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Second wave positive psychology coaching with difficult emotions: Introducing the mnemonic of ‘TEARS HOPE’

Abstract: Although the Positive Psychology (PP) approach has only recently established itself as a specialism within coaching, there is already a fresh perspective beginning to take shape within the field. This second wave (Held, 2004, Lomas & Ivtzan, 2016) or PP2.0 (Wong, 2011) calls for us to embrace the dark sides along with the bright sides and to integrate the challenging and difficult aspects of human experience into our understanding of wellbeing and flourishing. The author welcomes this second wave (PP2), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…To date, many attempts have been made to implement some of the scientific findings from the mainstream and second-wave positive psychology in coaching (cf. Cilliers, 2011;Sims, 2017). Nevertheless, most of them rely on implementing singular components of positive psychology, such as a strength-based model of coaching (Elston & Boniwell, 2011;Linley, Biswas-Diener & Trenier, 2011;Oades, Crowe & Nguyen, 2009;Roche & Hefferon, 2013), or encouraging the use of Positive Psychology Interventions (PPIs) (Passmore & Oades, 2015, 2016 and positive psychology measures (Susing, Green & Grant, 2011), as well as applying some of the positive psychology theories to the coaching practice (Foster & Lloyd, 2007).…”
mentioning
confidence: 99%
“…To date, many attempts have been made to implement some of the scientific findings from the mainstream and second-wave positive psychology in coaching (cf. Cilliers, 2011;Sims, 2017). Nevertheless, most of them rely on implementing singular components of positive psychology, such as a strength-based model of coaching (Elston & Boniwell, 2011;Linley, Biswas-Diener & Trenier, 2011;Oades, Crowe & Nguyen, 2009;Roche & Hefferon, 2013), or encouraging the use of Positive Psychology Interventions (PPIs) (Passmore & Oades, 2015, 2016 and positive psychology measures (Susing, Green & Grant, 2011), as well as applying some of the positive psychology theories to the coaching practice (Foster & Lloyd, 2007).…”
mentioning
confidence: 99%
“…Some authors mentioned that personal growth and development is a continuing process, which stretches beyond the confines of the coaching session (Tarragona, 2015). Learnings from the coaching sessions need to be transferred to the work environment in order to aid the client to practice the skills learned during coaching and to take ownership of the learning process (Passmore and Oades, 2014;Sims, 2017). Providing clients with "homework" between sessions increases engagement with and adherence to the coaching process (Frisch, 2013), whilst it provides an active means (in a safe environment) to develop and grow (Tarragona, 2015).…”
Section: Common Elements Of Positive Psychological Coaching Modelsmentioning
confidence: 99%
“…Further, the coach should identify appropriate positive psychological self-administered activities aligned to the strengths of the client, in order to ensure that significant gains in the client's positive state are facilitated (e.g., the gratitude visit; van Zyl et al, 2016a,b). These evidencebased positive psychological practices need to be aligned to the content of a given coaching session, they needs to be challenging (though not demanding), there should be an opportunity to actively practice such at work (van Zyl et al, 2016b) and they should be aimed at the active development of skills (Sims, 2017). The client should be requested to develop a portfolio of evidence while practicing these activities and developing their skills (Stander, 2016).…”
Section: Common Elements Of Positive Psychological Coaching Modelsmentioning
confidence: 99%
“…Researches have shown that the most commonly expressed difficult emotions in women include anger, frustration, regret, guilt, confusion and anxiety, and with these emotions there is a feeling of being uncomfortable and not at ease after expressing it (deMarris & Tisdale, 2002). A helpful coping strategy to deal with difficult emotions is a positive psychology technique called TEARS HOPE technique which is an acronym where T stands for Teach and learn, E stands for Express and Enable, A stands for Accept and befriend, R stands for Reappraise and reframe, S stands for Social support, H stands for Hedonic well-being, O stands for Observe and attend to, P stands for Physiology and behavioral changes, E stands for Eudaimonia this technique is based on the idea that experiencing positive emotions can help in dealing with difficult or negative emotions or the 'good' can help deal with 'bad' (Sims, 2017). Some other helpful coping strategies proved through various research studies to be effective include mindfulness techniques (Altinyelken, 2018) self-exercise, gratitude letter, journaling, sharing feelings, and taking a mental health day.…”
Section: Introductionmentioning
confidence: 99%